Recent Acceleration of Arabian Sea Warming Induced by the Atlantic‐Western Pacific Trans‐basin Multidecadal Variability - Cheng Sun; Jianping Li; Fred Kucharski; In‐Sik Kang; Fei‐Fei Jin; Kaicun Wang; Chunzai Wang; Ruiqiang Ding; Fei Xie (Geophysical Research Letters)
Abstract Arabian Sea (AS) warming has been significantly accelerated since the 1990s, in particular in the spring season. Here we link the AS warming changes to the Atlantic multidecadal oscillation (AMO). A set of Atlantic pacemaker experiments with a slab mixed‐layer ocean model successfully reproduces the AS spring multidecadal variability and its connection with the AMO. An atmospheric teleconnection from the Atlantic to the AS in the preceding winter and associated thermodynamic air‐sea feedback is found to be important. The teleconnection can be reestablished by the atmospheric model when the AMO sea surface temperature (SST) and its trans‐basin footprint over the western Pacific are prescribed simultaneously. The western Pacific SST warming associated with the AMO positive phase induces a Gill‐type Rossby wave over the AS, showing anomalously low pressures and converging southerlies that weaken winter northerlies. Thus, the wind‐evaporation‐SST feedback results in and maintains the AS warm SST anomalies to the subsequent spring.